An improved method for paleoflood reconstruction from core sediments in the upper Yellow River - Pang, Hongli; Jia, Yunxia; Li, Fuqiang; Qin, Lin; Chen, Liying (Frontiers in Earth Science, 2023)
Fluvial deposits represent a sedimentary archive of paleohydrological information, which can be used to reconstruct unrecorded flood. A multi-index (grain size, End-Member model, geochemistry elements) approach of core sediments from upper Yellow River was used to reconstruct the flood history. High-resolution geochemical proﬁle of 20.71m-deep core was obtained by the XRF core scanner. A comparison of sediment grain size with geochemical element ratios showed that the correlation between sand content and ln(Zr/Ti) is better than ln(Zr/Rb) and ln(Zr/Fe), which indicating that ln(Zr/Ti) can be used as a grain size proxy for the core HHZ. Combined with the End-Member modeling analysis, flood energy index (FEI) was constructed to highlight flood signal and it has similar trend with sediment ln(Zr/Ti). Within the ﬂood record, coarsened grain size and increased of ln(Zr/Ti) suggest that high-frequency floods appear to occur in the early Holocene(11-6.5ka B.P.) and late Holocene (3.5-0ka B.P.), while low-frequency floods occurred in the middle Holocene (6.5-3.5ka B.P.). Extraordinary flood generated during 5.8ka B.P. 5.9ka B.P. was probably the largest magnitude that have occurred, which coincided with sharply increase of sedimentation rates from 0.14mm/yr to 0.48mm/yr. The ﬂood activities at the upper reach of the Yellow River are considered to respond to climate variability in relation with the monsoonal shift.